High significance measurement of the terrestrial neutrino flux with the Borexino detector. Issue 6 (May 2016) - Ianni, A; Agostini, M; Altenmüller, K; Appel, S; Bellini, G; Benziger, J; Bick, D; Bonfini, G; Bravo, D; Caccianiga, B; Calaprice, F; Caminata, A; et al.
Abstract: We review the geoneutrino measurement with Borexino from 2056 days of data taking.